2015
DOI: 10.1039/c5cc06819c
|View full text |Cite|
|
Sign up to set email alerts
|

Coordination-directed self-assembly of a simple benzothiadiazole-fused tetrathiafulvalene to low-bandgap metallogels

Abstract: Coordination-driven gelation of a benzothiadiazole-fused tetrathiafulvalene (TTF) is demonstrated. This is the first work reporting highly stable metallogels based on a donor-acceptor conjugate with such a simple structure for the construction of new low-bandgap materials with various functional properties and novel nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The design of coordination polymers with a predictable secondary building unit (SBU) and dimensionality is a quasi-impossible task but the quest remains of great interest for the discovery of new materials with desired properties such as gas adsorption, [1][2][3][4][5][6][7][8][9] sensing, [10][11][12][13][14][15] thermochromism, [16][17][18][19] magnetism, [20][21][22][23][24] conductivity, [25][26][27][28] redox-activity, 29,30 catalysis, 13,[31][32][33] nonlinear optical behavior 34,35 and luminescence. 8,[36][37][38][39][40] Recent reviews on CPs formed by mono-and dithioethers with CuX salts (X = Cl, Br, I) [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…The design of coordination polymers with a predictable secondary building unit (SBU) and dimensionality is a quasi-impossible task but the quest remains of great interest for the discovery of new materials with desired properties such as gas adsorption, [1][2][3][4][5][6][7][8][9] sensing, [10][11][12][13][14][15] thermochromism, [16][17][18][19] magnetism, [20][21][22][23][24] conductivity, [25][26][27][28] redox-activity, 29,30 catalysis, 13,[31][32][33] nonlinear optical behavior 34,35 and luminescence. 8,[36][37][38][39][40] Recent reviews on CPs formed by mono-and dithioethers with CuX salts (X = Cl, Br, I) [41][42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
“…In general, the rational design behind these examples involves the connection of the TTF unit with groups capable of H-bonding, such as urea [57] or amide groups [58][59][60][61][62][63], to form extended structures. The incorporation of other molecular building blocks commonly used to form physical gels [64][65][66][67] or the use of metal-organic interactions [68][69][70] have also been employed to form TTF-based gels. Moreover, the inclusion of hydrophobic aliphatic chains is also employed to facilitate van der Waals interactions and stabilize the supramolecular aggregates [58][59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of other molecular building blocks commonly used to form physical gels [64][65][66][67] or the use of metal-organic interactions [68][69][70] have also been employed to form TTF-based gels. Moreover, the inclusion of hydrophobic aliphatic chains is also employed to facilitate van der Waals interactions and stabilize the supramolecular aggregates [58][59][60][61][62][63][64][65][66][67][68][69][70][71]. If formation of CT complexes takes place, the TTF unit will bear positive charge, which can alter the interaction of neighboring TTF units and influence the intermolecular interactions arising from other groups involved in the self-assembly process.…”
Section: Introductionmentioning
confidence: 99%
“…For other applications,L iu et al reported BTD-TTF as al owmolecular-weight gelator in the presence of certain transitionmetal halide salts ( Figure 5). [51] This self-assembly process is mainly driven by the coordination ability of the BTD moiety to metal ions. Liu et al reported MP-TTF for application in dyesensitised solar cells ( Figure 5).…”
Section: Ttf Derivatives With Electron-withdrawing Groupsmentioning
confidence: 99%